Base Erosion and Profit Shifting in the Digital Economy: A Bibliometric and Quantitative Synthesis of Emerging International Tax Norms - Akbar, Arya Zulfikar; Rizqi, Reza Muhammad; Martadinata, Sudrajat; Norzihad , Fatin Nabilah (Manunggal Halim Jaya, 2026)
This study examines the evolution of academic discourse on Base Erosion and Profit Shifting (BEPS) in response to the digitalization of global commerce, focusing on the OECD/G20 Two-Pillar Solution and its implications for advanced and developing economies. Using a multi-method approach, the research combines a systematic literature review, bibliometric mapping with VOSviewer 1.6.20, and quantitative synthesis comparable to meta-analysis. The corpus consists of 60 sources, including 50 peer-reviewed journal articles and 10 authoritative policy documents published between 2013 and 2025. Bibliometric analysis identifies five dominant thematic clusters in BEPS scholarship and shows an average annual publication growth of approximately 32% after 2015. Quantitative synthesis of 28 empirical studies produces a pooled standardized effect size of d = 0.42 with a 95% confidence interval of 0.31–0.53, indicating moderate and statistically significant policy effectiveness, though with substantial heterogeneity. Findings suggest that digital services taxes have moderated profit-shifting behavior, while Pillar One faces political resistance and Pillar Two’s GloBE Rules create compliance burdens, especially for lower-income jurisdictions. The study provides policy and scholarly insights into post-BEPS international tax governance.